The decision to study abroad at Hungarian university: for what benefits International students are looking for? - Borodina, Daria; Estrela, Ádrian (GILE Journal of Skills Development, 2023)
Globalisation is driving the internationalisation of higher education, promoting open access to universities, enhancing educational programs with an international focus, and stronger presence in the international higher education market. Thus, globalisation stimulates the internationalisation of universities. For universities to attract international students successfully, it is necessary to understand general issues regarding the decision-making process. The study aims to analyse the benefits of studying abroad at a Hungarian university among international students. To fulfil the aim of this study, a questionnaire was administered to 100 international students, aged 18 to 38. The study results showed that international students had been looking for benefits while studying abroad, such as personal development, cultural experience, career prospects, and the possibility of travelling. Some benefits were also related to social and economic factors such as access to unique courses and knowledge, positive country image, safety situation, and affordable living costs in Hungary. The decision to study at a Hungarian university was made according to such benefits, including a desired program of study, comfortable facilities, flexible schedule, admission criteria, opportunity to improve English language skills, good reputation of the university, European degree, supportive environment, related costs, and future career prospects. At the same time, different age groups of international students considered the importance of benefits differently. Also, different groups of international students based on perceived social family status paid attention to different benefits. The findings of this study can be used for the promotion of Hungarian universities internationally to attract more international students with benefits that they look for when studying abroad.